2019
DOI: 10.1111/joop.12273
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a commitment to organizational career scale: At the crossroads of individuals’ career aspirations and organizations’ needs

Abstract: This paper introduces the construct of commitment to organizational career (COC). Conceptualized as a specific form of goal commitment, COC reflects an individual's commitment to the goal of pursuing a long and successful career in an organization. We developed a 5‐item measure of COC and examined its validity and reliability in four studies involving employees from diverse organizations and occupations (Ns = 312, 187, 199, 309). We explore COC's distinctiveness from related constructs, including organizationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 83 publications
(150 reference statements)
0
20
0
Order By: Relevance
“…Indeed, the discriminant validity of career commitment from measurements of organizational commitment and job involvement has been captured by a good deal of empirical studies (e.g. Gebbels et al, 2020;Lapointe et al, 2019). According to Colarelli and Bishop (1990), in contrast to career commitment, organizational commitment should be viewed as loyalty or emotional attachment to the current working organization rather than to the vocation.…”
Section: Career Commitment Career Commitment and Other Forms Of Work Commitmentmentioning
confidence: 99%
“…Indeed, the discriminant validity of career commitment from measurements of organizational commitment and job involvement has been captured by a good deal of empirical studies (e.g. Gebbels et al, 2020;Lapointe et al, 2019). According to Colarelli and Bishop (1990), in contrast to career commitment, organizational commitment should be viewed as loyalty or emotional attachment to the current working organization rather than to the vocation.…”
Section: Career Commitment Career Commitment and Other Forms Of Work Commitmentmentioning
confidence: 99%
“…Following Lapointe et al [ 70 ], we adopted three items to measure employees’ turnover intention: “I often think about leaving my organization”, “I am actively searching for a job at another organization”, and “If I could choose again, I would choose to work for another organization” (Cronbach’s α = 0.87).…”
Section: Methodsmentioning
confidence: 99%
“…Fifth, our study focused on affective commitment as it has been found to have a stronger relationship with OCBs than other dimensions of commitment (Cetin et al, 2015). Future research could also study other conceptualizations of organizational commitment, such as normative and continuance commitment (Allen & Meyer, 1990) and commitment to organizational career (Lapointe et al, 2019), in conjunction with affective commitment to develop a more comprehensive perspective of the role of organizational commitment.…”
Section: Limitations and Future Researchmentioning
confidence: 99%